The Predictors of the Severity of Dengue Fever: A Cross-Sectional Study in a Tertiary Care Center of Bangladesh (Journal of Dhaka Medical College, 2021)
Background: Dengue is an endemic disease for Bangladesh with occasional outbreak. Little is known about the predictors of severe dengue.Methods: This cross sectional study was conducted in the medicine department of Dhaka Medical College from April 2019 to March 2020. Total 199 consecutive patients were enrolled in this study. For the purpose of the analysis, dengue fever was classified as group I and dengue hemorrhagic fever and dengue shock syndrome was classified as group II.Results: The mean (SD) age of the study population was 28.5(12.1) and 87.4% were less than 40 years of age. The male and female ratio was about 3:1. Among the total study population, 149(74.9%) patients had DF, 46 (23.1%) had DHF and only 4 (2%) had DSS on presentation. Baseline demography and clinical presentation did not significantly differ between classical dengue and severe dengue. Previous history of dengue had low association with severity (RR, 95%CI, phi, P value; 1.2, 1.04-1.40, 0.25, 0.001).Most of the laboratory parameters were similar between the groups. The number of platelet count was significantly lower in DHF and DSS [median (IQR) 43500(16500-95250], than DF [median (IQR) 65000(33000-1170000, p-value 0.01]Conclusion: Previous infection with dengue virus and decreasing platelet count are the predictors of the severe dengue.J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 77-82